Monitoring strain development of soil slope using distributed optical fibre sensor. (May 2019) - Awang Ismail, Dayangku Salma bt; Kassim, Azman; bin Mohamad, Hisham; A Rashid, Ahmad Safuan; Bunawan, Aliff Ridzuan
Abstract: Rainfall infiltration is well-known as one of the important factors that lead to slope failure in tropical areas such Malaysia because it's significant fluctuation of pore water pressure due to monsoon seasons. In this paper, a distributed sensing optical fibre system named Brillouin Optical Time Domain Analysis (BOTDA) is used to monitor the strain development of a laboratory soil slope model. The aim of study is to determine the plane failure of a residual soil slope under rainfall infiltration and subsequent loading impact using BOTDA technology. A soil slope model was constructed from Malaysian residual soil slope and tested under various rainfall infiltration patterns and sequential loadings. A continuous ribbon optical fibre has been directly embedded in the soil slope to measure the soil strain. The paper only presented on soil strain response due to rainfall infiltration and relations to the pore pressure development within the finite slope. From the experiments, it has been observed that the optical fibre has been able to capture soil strain during infiltration which proven the sensitivity of optical fibre to measure soil strain. The maximum strain observed was about 850 microstrain (µε) which occurred at the third layer of slope height (L1) at 8-hour of infiltration. After 24-hours of infiltration, the strain was observed to be constant for all layers; Layer 1 (L1) = 302 µε, Layer 2 = 210 µε and Layer 3 (L3) = 190 µε in which the whole sample was clearly seen in a fully saturated condition and the negative pore pressure has remained constant throughout the depth.